Combined additive manufacturing approaches in tissue engineering. (15th September 2015) - Giannitelli, S.M.; Mozetic, P.; Trombetta, M.; Rainer, A.
Graphical abstract: Abstract: Advances introduced by additive manufacturing (AM) have significantly improved the control over the microarchitecture of scaffolds for tissue engineering. This has led to the flourishing of research works addressing the optimization of AM scaffolds microarchitecture to optimally trade-off between conflicting requirements (e.g. mechanical stiffness and porosity level). A fascinating trend concerns the integration of AM with other scaffold fabrication methods ( i.e. "combined" AM), leading to hybrid architectures with complementary structural features. Although this innovative approach is still at its beginning, significant results have been achieved in terms of improved biological response to the scaffold, especially targeting the regeneration of complex tissues. This review paper reports the state of the art in the field of combined AM, posing the accent on recent trends, challenges, and future perspectives.